Systematic review on Screening for antimicrobial-resistant Gram-negative bacteria in inpatients. (30th September 2020) - Scardina, G; Arzilli, G; Casigliani, V; Moi, M; Lucenteforte, E; Petri, D; Rello, J; Manissero, D; Lopalco, P L; Tavoschi, L
Abstract: Background: Infections with antimicrobial-resistant Gram-negative bacteria (AMR-GNB) are increasingly being reported worldwide. Early identification of carriage at hospital admission is essential to reduce the risk of onward transmission within the health facility. This systematic review aimed at exploring screening practices for AMR-GNB faecal colonization among patients on admission to hospital in high-income countries and estimating its prevalence. Methods: We searched on Pubmed, Scopus and Cochrane databases for studies published from 2010 up to April 2019. We included studies reporting on patients ≥18 years old and hospitalised (excluding long-term care facilities). Results: The search retrieved 9496 articles, 85 were included after screening: 10 reported screening activities in outbreak situations (not included in the analysis); 75 in non-outbreak situations. Based on the target patient groups and setting we identified four subsets of screening approaches: all admitted (AA) in high risk (HR) wards (36 studies, 48%), HR patients in HR wards (12, 16%), HR patients in low risk wards (LRW) (11; 15%) and AA - LRW (15, 20%). HR patients-based screening targeted patients with certain clinical conditions (mostly oncologic patients, 37%), travellers 29%, previously hospitalised and individuals with multiple risks 34%. HR wards-based screening was performed mostly in ICU (73%), while LRW-based screening in hospital-wide setting (58%). We investigated the overall prevalence rates of AMR-GNB (15.1%; 95%CI: 9.5-21.6), Klebsiella spp (KB) (4.1%; 3.1-5.3), E. coli (9.6%; 7.7-11.7) P. Aeruginosa (7.6%; 1.7-16.8), A. Baumannii (2.1%; 0.5-4.4) and other Enterobacterales (0.8%; 0.59-1.1). Reported KB-prevalence varied according to screening approaches, with statistically significant higher prevalence in HR wards. Conclusions: According to our data, screening for AMR-GNB mostly followed targeted approaches. Overall prevalence of AMR-GNB carriage at hospital admission was considerable. Key messages: This systematic review gives un overview on the screening procedures for AMR-GNB faecal colonization among patients on hospital admission in high-income countries. According to our results, overall prevalence of AMR-GNB carriage was considerable (15.1%), varying among specific pathogens but with no significant correlation with screening approaches, except for KB.